Technology adoption in architectural design studios for educational activities - Hassanpour, Badiossadat; Sahin, Nil Pasaoglulari (Routledge Journals, Taylor & Francis Ltd, 2021)
Technology in architectural education is usually discussed as a 'method', optimising course systems and determining instructional materials, while as a 'tool' it is discussed as a medium within students' design decision-making processes. This article explores the development of technology use in a teaching context, encompassing relationships between technology as method and tool. The teaching focus concerns the effects of technological-instructional tactics for addressing commonly reported issues for architecture students: being reflexive to instructional inputs, avoiding mental shortcuts and prioritising forecasting when making design decisions. The article reports a multi-phase action research project, exploring how a supplementary digital toolkit can address genuine, contextually driven problems in disciplinary teaching. Findings highlight how developing technological-instructional tactics in design studios can assist students to comprehend instructors' intentions, support dialogue between students and instructors (especially in longitudinal activities), and transform how teachers perform roles as advisors and coaches.
Keywords: Technology; technological-instructional tactic; architectural design studio; decision-making process; hybrid action research